2021
DOI: 10.48550/arxiv.2102.03109
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Estimation of Microphone Clusters in Acoustic Sensor Networks using Unsupervised Federated Learning

Abstract: In this paper we present a privacy-aware method for estimating source-dominated microphone clusters in the context of acoustic sensor networks (ASNs). The approach is based on clustered federated learning which we adapt to unsupervised scenarios by employing a light-weight autoencoder model. The model is further optimized for training on very scarce data. In order to best harness the benefits of clustered microphone nodes in ASN applications, a method for the computation of cluster membership values is introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…For both 4SA and 2SL scenes, we can indeed observe the aforementioned effects for the first four and two columns, respectively. When compared to [15] and [19], which both use unfurnished shoebox rooms, it can be observed that the results generated by the improved version of unsupervised CFL proposed in this work show great potential, especially for the 2SL scene which clearly outperforms [19].…”
Section: Clusteringmentioning
confidence: 89%
See 4 more Smart Citations
“…For both 4SA and 2SL scenes, we can indeed observe the aforementioned effects for the first four and two columns, respectively. When compared to [15] and [19], which both use unfurnished shoebox rooms, it can be observed that the results generated by the improved version of unsupervised CFL proposed in this work show great potential, especially for the 2SL scene which clearly outperforms [19].…”
Section: Clusteringmentioning
confidence: 89%
“…Moreover, hardclustering without the possibility of generating membership values has been used. We have recently addressed some of the aforementioned aspects and successfully explored the application of an unsupervised CFL clustering scheme in ASNs [19]. However, the latter work is also limited to a shoebox room with only two simultaneously active sources and, consequently, only two clusters.…”
Section: Relation To Prior Workmentioning
confidence: 99%
See 3 more Smart Citations